2016
DOI: 10.3389/fncir.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Potentiation at Temporoammonic Path-CA1 Synapses in Freely Moving Rats

Abstract: Hippocampal area CA1 receives direct entorhinal layer III input via the temporoammonic path (TAP) and recent studies implicate TAP-CA1 synapses are important for some aspects of hippocampal memory function. Nonetheless, as few studies have examined TAP-CA1 synaptic plasticity in vivo, the induction and longevity of TAP-CA1 long-term potentiation (LTP) has not been fully characterized. We analyzed CA1 responses following stimulation of the medial aspect of the angular bundle and investigated LTP at medial tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…However, at IPI 25 ms, EC-induced PPF was hardly noticeable (PPF 1.1 ± 0.2, n=4). These findings are in agreement with those reported in previous studies (Sloviter 1991;Leung et al 1995;Dolleman-van der Weel et al 1997;Eleore et al 2011;Ito and Schuman 2012;Gonzalez et al 2016). …”
Section: Ca1 Responses To Paired Pulse Stimulation Of Re and Ecsupporting
confidence: 83%
“…However, at IPI 25 ms, EC-induced PPF was hardly noticeable (PPF 1.1 ± 0.2, n=4). These findings are in agreement with those reported in previous studies (Sloviter 1991;Leung et al 1995;Dolleman-van der Weel et al 1997;Eleore et al 2011;Ito and Schuman 2012;Gonzalez et al 2016). …”
Section: Ca1 Responses To Paired Pulse Stimulation Of Re and Ecsupporting
confidence: 83%
“…On the basis of recent establishment of in vivo perforant pathway LTP recording (Aksoy‐Aksel & Manahan‐Vaughan, ; Gonzalez, Villarreal, Morales, & Derrick, ), the role of synaptic Zn 2+ in perforant pathway LTP was examined by our original approach, in which a recording electrode attached to a microdialysis probe was used and the recording region was locally perfused with Zn 2+ chelators in ACSF via the microdialysis probe. Perforant pathway LTP was not attenuated under perfusion with CaEDTA (10 mM), but attenuated under perfusion with ZnAF‐2DA (50 μM), suggesting that intracellular Zn 2+ signaling is required for perforant pathway LTP as well as Schaffer collateral LTP (Takeda et al, ) (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that intracellular Zn 2+ signaling, which originates in internal stores/proteins, is involved in LTP at perforant pathway–CA1 pyramidal cell synapses (Figure ). Because perforant pathway LTP may be induced NMDA receptor‐dependently (Gonzalez et al, ), it is likely that NMDA receptor activation triggers off Zn 2+ release from internal stores. Stork and Li () report that Zn 2+ is released from thapsigargin/IP3‐sensitive stores in cultured cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo studies demonstrate that LTP that lasts in excess of 24 h can be evoked by tetanic stimulation in freely behaving rats [56,64]. Further investigation found that this form of in vivo LTP is dependent on NMDA receptor activation [64]. Moreover, in hippocampal slices (P30-50), stimulation of proximal TA inputs induces LTP at distal SC-CA1 synapses when the two inputs are paired at a precise time interval [65].…”
Section: Long Term Potentiation (Ltp) At Ta-ca1 Synapsesmentioning
confidence: 99%
“…Furthermore, GluA2-lacking AMPA receptors are required for the maintenance, but not induction of HFS-induced LTP at juvenile TA-CA1 synapses [59]. Recent in vivo studies demonstrate that LTP that lasts in excess of 24 h can be evoked by tetanic stimulation in freely behaving rats [56,64]. Further investigation found that this form of in vivo LTP is dependent on NMDA receptor activation [64].…”
Section: Long Term Potentiation (Ltp) At Ta-ca1 Synapsesmentioning
confidence: 99%